(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2022)
In general, this article points to a broader reflection on the interest oberserved in contemporary historians to study the soldiers who were protagonists of the counterinsurgency, both in Mexico and in other parts of Latin America. In particular, it aims to analyze the Mexican and Mexicanist historiographical production that in recent decades has been generated around the figure of the Spanish soldier and political, Felix Maria Calleja, identify topics of interest and suggest new lines of research.